2013
DOI: 10.1371/journal.pone.0079337
|View full text |Cite|
|
Sign up to set email alerts
|

Oyster Larvae Settle in Response to Habitat-Associated Underwater Sounds

Abstract: Following a planktonic dispersal period of days to months, the larvae of benthic marine organisms must locate suitable seafloor habitat in which to settle and metamorphose. For animals that are sessile or sedentary as adults, settlement onto substrates that are adequate for survival and reproduction is particularly critical, yet represents a challenge since patchily distributed settlement sites may be difficult to find along a coast or within an estuary. Recent studies have demonstrated that the underwater sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 46 publications
5
100
0
1
Order By: Relevance
“…The potential impacts of increased ocean noise on marine animals' reproduction [Lillis et al, 2013], feeding [Simpson, 2005], communication [Edds-Walton, 1997], and physiology [Rolland et al, 2012] have raised concerns about ecosystem health. Studies have shown that the distance to major ports and shipping lanes, changes in shipping routes, as well as economies and regulatory policies, may affect low-frequency noise levels [Miksis-Olds et al, 2013;McKenna et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The potential impacts of increased ocean noise on marine animals' reproduction [Lillis et al, 2013], feeding [Simpson, 2005], communication [Edds-Walton, 1997], and physiology [Rolland et al, 2012] have raised concerns about ecosystem health. Studies have shown that the distance to major ports and shipping lanes, changes in shipping routes, as well as economies and regulatory policies, may affect low-frequency noise levels [Miksis-Olds et al, 2013;McKenna et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…When larvae are preparing to settle, vertical position can be especially important in permitting them to identify and investigate suitable settlement sites (e.g., [23,24,4]). Some examples of physical cues for the regulation of vertical position include turbulence (Chapters 2, 3, 4, [25,26,27,28,29]), sound [30], and light (Chapter 5, [31,32,33,34,35]). Cues incorporating biological and chemical signals include exudates from predators [36,37], prey or host species [38,39], and conspecific settlement sites (Chapter 6, [40,41]).…”
Section: Contentsmentioning
confidence: 99%
“…Indeed, larval oysters appear to use acoustic signatures typical of oyster reefs [30] and chemical cues released by adult oysters [95] to initiate settlement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the effect of light and turbulence on specific 37 characteristics of helical trajectories, and found that these environmental cues induce changes to due to a combination of overharvesting and long-term environmental changes (Rothschild et al 55 1994, Kemp et al 2005), and efforts at population restoration and conservation require us to study oysters at the vulnerable larval stages. Understanding larval behavior during planktonic 57 stages is important for both dispersal modelling (North et released by adult oysters to initiate settlement (Tamburri et al 1996), and more recent work 71 suggests a possible role of acoustic signatures typical of oyster reefs (Lillis et al 2013). …”
mentioning
confidence: 99%